Using Economic Incentives to Encourage Sustainable Alternative Residential Landscaping Practices in Florida - Hayk Khachatryan; Alicia Rihn; Xumin Zhang; Michael Dukes (EDIS)
This report is the third in a series from the Sustainable Residential Landscape Project. This report summarizes Floridian homeowners’ interest in and response to economic incentives to encourage the installation of more sustainable alternative residential landscapes based on a survey. Written by Hayk Khachatryan, Alicia Rihn, Xumin Zhang, and Michael Dukes, and published by the UF/IFAS Food and Resource Economics Department, July 2022.